WHAT WOULD BE THE AGE TO ENTER THE REFEREEING BOARD OF CBF? (Fiep Bulletin - online, 2011)
Recently, the national press aired that determination of the Arbitration Commission of the Brazilian Football Confederation (CBF), the referee maximum age to be part of the national board would be reduced from 35 to 30 years, and that decision was taken without presentation of any scientific basis. Therefore, the aim of this study was to determine whether there are significant differences between the physical performance of a referee aged 30 years compared with an over 40 years. To that end, this research was developed based on bibliography, which used as a theoretical, scientific articles published in specialized journals. To test the likelihood of variations in age-related physical fitness and performance, Castagna et al. (2005) separated by age, one group of referees. After analyzing the results, the authors concluded that the distances the three groups during the Cooper test, no showed statistically significant differences between them (p>0.05). Although go (cover) less total distance and perform less sprints, referees older (43 - 48 years) were able to maintain an average distance of infractions that were comparable to those reported by umpires youth (31 - 36 years) (Weston et al. 2008). Spanish researchers (CASAJUS and CASTAGNA, 2006), observed that both VO2max. as in 12-minute test, the variables related strongly with race performance during the game (D'Ottavio and CASTAGNA, 2001; CASTAGNA et al. 2002b) showed no significant difference between age groups in the development study. These findings suggest that older referees have aerobic performances similar to those shown by their younger colleagues.
Keywords: referee; soccer; age